PENGELOLAAN DATABASE PRODUK UMKM PURWOREJO DI YODOTUKU.COM BERBASIS MICROSOFT ACCESS 2016 - , (Jurnal Akuntansi Pajak dan Manajemen (TAJAM), 2023)
Yodotuku.com which has been running recently has had many obstacles, one of which is product data processing, such as in the data search process. This study aims to find out how to manage the database of Purworejo UMKM products at Yodotuku.com based on Microsoft Access 2016 to support the company's operational activities in terms of program design and program implementation. This study aims to find out how to manage the database of Purworejo UMKM products at Yodotuku.com based on Microsoft Access 2016 to support the company's operational activities in terms of program design and program implementation